Evaluating Financial Health and Sustainability of Post-Merger Port Operations in Indonesia: Liquidity and Profitability Insights - Liwaul, Liwaul; Dali, Nasrullah; Sahrun, Sahrun (JASF: Journal of Accounting and Strategic Finance, 2023)
This study aims to analyze the financial health of PT Pelabuhan Indonesia (PT Pelindo) after the merger with a liquidity and profitability assessment approach for the sake of the company's survival in global economic turmoil and increased digital services for consumers who use transportation services. The method used is secondary data in the form of audited financial statements (2021-2023). This research uses a descriptive quantitative approach by analyzing the company's liquidity, profitability, and efficiency. The analysis technique uses liquidity financial ratio analysis, including current, quick, and cash ratios. In contrast, profitability ratios include gross profit margin (GPM), net profit margin (NPM), return on assets (ROA), and return on equity (ROE) to describe the company's financial health condition. The results and discussion of the study indicate that the Indonesian port company (PT Pelindo), after the merger from 2021 to 2023 suggests that it needs to implement a liquidity strategy through financial restructuring with a focus on managing current assets and current liabilities, increasing cash efficiency, accelerating collections, and reviewing capital structure to ensure liquidity remains adequate and reduce liquidity risk, especially with the downward trend in cash ratio which can threaten the company's stability in the future. Improving the profitability of Indonesian port companies should focus on operational cost efficiency, including digitalization, process and preventive maintenance, and collaborating with strategic partners to increase revenue, diversify port services, and optimize asset usage to maintain long-term financial stability and minimize negative impacts and external fluctuations.